THE IMPACT OF TAXATION AS AN AID TO ECONOMIC DEVELOPMENT (APPLIED STUDY IN KURDISTAN REGIONAL GOVERNMENT) - Ahmed, Amanj Mohamed; Ali, Muhammad Nawzad (Studies and Scientific Researches. Economics Edition, 2020)
This research was carried out to determine the weight of taxation in economic development, the main purpose is to discover the level of impact of taxation on economic development or if it has any impact. Another key objective is to improve the level of understandability and find probable solutions toward issues in taxation within the Kurdistan region, as well as unveiling the Kurdistan Regional Government’s taxation system in compliance with the up to date old Iraqi tax laws. KRG is barely surviving this crisis, with the increase of unemployment and poverty could taxation work as an aid to support the piles of the region. The current corruption in the government that does not use tax money efficiently and lack of transparency has been evaluated. Primary and secondary research methods were used to be able to gather information in order to reach an understanding. The primary source of data includes personal interviews and questionnaires, meanwhile, the secondary source of data includes the use of textbooks, social media, internet, and newspapers. Non-probability method of sampling was used in selecting the respondents. The study used the standard deviation, chi-square formula, and tables for the method of the examination. The results clearly illustrates that the government should commence the critical pursuit of broadening regional economy in order to improve economic growth and expansion and to become meticulous to fight with real corruption. The limitation and resources should be expanded by the government and bring taxation back to life through educational systems and social awareness.